Pelaksanaan Pembelajaran dalam Memahami Kosakata Benda di Masa Pandemi Pada Siswa Tunarungu Kelas 2 - Fyrda Rosalina Rais; Ishak G Bachtiar; Etty Hasmayati (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This study aims to determine the description of the implementation in understanding the vocabulary of object for deaf children at SLB Negeri Bekasi Jaya. This research uses a qualitative approach with descriptive methods. The data used in this study swew obtained through speaches from the informants and actions observations in the field. Data collection techniques used are by conducting observations in the field,I nterviews with class teachers and document study. The findings obtained in this study are schools apply learning in understanding the vocabulary of object it’s using the vocabulary card.The strategy used by teacher is ekspository strategy and using the question and answer method. The learning program be adapted based on the results of the assessment carried out on new student admissions. The beginning students mentioning the teachers words, then students classification vocabulary of object, and pair the vocabulary of object. Students are understanding the vocabulary of object when students can pair vocabulary of object card images with their own writing oneself without the help of parents. Supporting factors in understanding the vocabulary of object is students can be conducive and good parental cooperation. The obstacle experienced by the teachers its students easily lose focus during distance learning.